A comprehensive review on the atomization and spray characteristics of renewable biofuels. (March 2023) - Mehra, Kuber Singh; Pal, Jyoti; Goel, Varun
Graphical abstract: Highlights: Macroscopic and microscopic characteristics of biofuels spray are discussed. Experimental and computational advancement are explored. Role of cavitation and heat and mass transfer in the spray is studied. Opportunities and challenges associated with the viability of renewable fuels are discussed. Abstract: Due to sustainability, rising energy demands, environmental concerns and energy security issues, scientists and researchers around the world are studying renewable biofuels as an alternative to fossil fuels. Biofuels or alternative fuels such as biodiesel, pure plant oil, DME (dimethyl ether) and alcohols which are derived from different renewable biomass sources were investigated by the scientific community as a substitute fuel for diesel engines. The spray process plays the main role in the proper combustion of fuel in engines, leading to a decrease in tailpipe emissions and an increase in engine efficiency. Development in the understanding of biofuel spray characteristics results in low emissions compared to fossil fuels and thus making biofuels a sustainable option for the future. Since, fuel properties have a significant impact on spray development, hence numerous experimental and computational studies were conducted. This article critically examines the atomization and spray characteristics of various alternative fuels utilized for diesel engines. In addition, recent advances and progress in numerical modeling and simulation of the biodiesel spray process are also discussed. To meet renewable fuels viability in CI (compression ignition) engines as a substitute to diesel fuel, various associated challenges and their probable solutions are also discussed.